Association of Vitamins with Type 2 Diabetes Mellitus - Durgeshwar, MD, Dr. Kumar; Yadav, MD, Dr. Rajkumar; Singh, MD, Dr. Suman Kumar (International Journal of Innovative Research in Medical Science, 2018)
The cases of DM are increasing rapidly at an alarming rate all over the globe. About 415 million adults are suffering from the disease all around the world according to the International Federation of Diabetes. It is also estimated that by the year 2040 the number of people suffering from diabetes will reach around 642 million [1]. The number of adults with diabetes has quadrupled to 422 million since 1980 according to the first global report on Diabetes by World Health Organization [2]. Type 2 diabetes mellitus is a serious problem of public health in India associated with dietary shift, genetic susceptibility and lifestyle changes [3]. According to a study it has been found that diabetes is gaining the status of epidemic in India with more than 62 million people diagnosed with the disease. [4,5].